1998
DOI: 10.1093/ajcn/67.6.1111
|View full text |Cite
|
Sign up to set email alerts
|

Childhood obesity and adult cardiovascular mortality: a 57-y follow-up study based on the Boyd Orr cohort

Abstract: Few studies have examined associations between childhood overweight and adult disease. We examined the relation between BMI measured in childhood and adult all-cause and cardiovascular mortality in a 57-y follow-up of a cohort study based on the Carnegie (Boyd Orr) Survey of Family Diet and Health in prewar Britain (1937-1939). Complete baseline and follow-up data were available for 1165 males and 1234 females who were aged between 2 y and 14 y 9 mo when they were examined. All-cause and cardiovascular mortali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
301
2
12

Year Published

2003
2003
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 476 publications
(327 citation statements)
references
References 22 publications
7
301
2
12
Order By: Relevance
“…13,28 Adolescent body size/composition has also been associated with subsequent adult health outcomes. 1,6,[29][30][31][32][33] These results provide further evidence for the prevention and treatment of childhood and adolescent obesity.…”
Section: Discussionmentioning
confidence: 94%
“…13,28 Adolescent body size/composition has also been associated with subsequent adult health outcomes. 1,6,[29][30][31][32][33] These results provide further evidence for the prevention and treatment of childhood and adolescent obesity.…”
Section: Discussionmentioning
confidence: 94%
“…Type 2 diabetes mellitus, systemic arterial hypertension, dyslipidemia, gastroesophageal reflux disease, osteoarthritis, orthopedic and postural problems, certain types of cancers in later phases of life, social adjustment problems and depression are some of the diseases associated with childhood obesity 2425 A British cohort study, carried out in late 1990, showed that being overweight during childhood resulted in a two-fold increase in the risk of death from ischemic heart disease in adulthood 26. Obesity is also related to obstructive sleep apnea-hypopnea syndrome, asthma and exercise intolerance 25…”
Section: Discussionmentioning
confidence: 99%
“…In the general pediatric population, epidemiologic data obtained from separate cohorts of obese children and adolescents of various ethnicities and from separate geographic regions have also demonstrated increased cardiovascular disease mortality later in adulthood 36, 37, 38, 39. Similar to the observed data reported from adults, strong associations between increased body mass index (BMI; calculated as kg/m 2 ) and systolic blood pressure (SBP) have been demonstrated in large population‐based pediatric studies such as NHANES III (Third National Health and Nutrition Examination Survey) 40…”
Section: Cardiovascular Risk Factors Among Asf Participantsmentioning
confidence: 99%